Analysis of Wakaf and Maqashid Syari'ah Law on the Development of Wakaf Property in Lhokseumawe City - Yasir Nasution; Alyasa’ Abubakar; Kafrawi (Britain International for Academic Research (BIAR) Publisher, 2021)
The development of waqf assets in the form of adding the function of waqf is a new phenomenon in the problems of Islamic law jurisprudence even in positive law in Indonesia. In national law (positive), Indonesia has regulated this issue with the existence of laws and government regulations regarding waqf both movable and immovable waqf assets, even in its development every property in waqf must have an Deed and / or certificate. Whereas in Islamic jurisprudence, the development of waqf assets in the form of additional functions is one of the problems that can be said to be new, it needs legal conclusions and even has to be seen from various theoretical concepts such as maqashidu sharia. Therefore this research will examine the issue of developing waqf assets based on the Waqf Law and maqashid syari'ah. This research is an empirical legal research using a sociological legal approach, with data collection through documentation and interviews. The results of the research show that the development of waqf assets is permitted according to the law, but with the stipulated conditions, besides that the development of waqf assets is also permissible in Islamic jurisprudence as long as it is solely for reasons in accordance with the concept of maqasidu syari'ah and the point is to seek maslahat.